Study on the frequency and chemical composition of urinary stones of Moghani sheep in Northwest of Iran - Nozohour, Y; Najarnezhad, V (Journal of the Hellenic Veterinary Medical Society, 2023)
Nephrolithiasis is one of the most important urinary tract diseases of ruminants and a costly problem for many sheep and goat owners. Therefore, it is important to analyse the composition of renal stone to prevent the formation of these kind of stones. The aim of the present study was to determine the frequency and the chemical constituents of urinary stones of Moghani sheep in Northwest of Iran. The kidneys, ureters, and urinary bladders of 384 Moghani sheep were examined carefully. The prevalence of urinary stones was 3.7%. All the stones were in the pelvis of the kidney and no stones were found in the ureter or urinary bladder. Macroscopically, 85.7% of the urinary stones showed a rough (jagged) appearance and 12.3% of them a smooth appearance. The largest and smallest urinary stones were 7 mm and 2 mm in diameter and 0.600 g and 0.087 g in weight, respectively. The composition of calculi were pure or mixed and included calcium oxalate (44.44%), magnesium ammonium phosphate (33.33%) and calcium carbonate (22.22%). Calcium oxalate was the major constituent in the urinary stone, hence, grazing on the pasture plants containing oxalate should be limited. More detail studies should be designed to clarify the contribution of environmental and nutritional factors in development of urinary stones.